Reduction in harmonic and Compensation of Reactive power in Photovoltaic fed circuit (International Journal of Food and Nutritional Sciences, 2022)
This research suggests an enhanced hybrid DSTATCOM for reactive and harmonic power adjustment that is fuelledby solar energy. A series-connected capacitor at the front end of the voltage source inverter and an LCL passive filteris used to connect the solar system to the grid.